Photodynamical analysis of the triply eclipsing hierarchical triple system EPIC 249432662. Issue 2 (22nd November 2018) - Borkovits, T; Rappaport, S; Kaye, T; Isaacson, H; Vanderburg, A; Howard, A W; Kristiansen, M H; Omohundro, M R; Schwengeler, H M; Terentev, I A; Shporer, A; Relles, H; et al.
ABSTRACT: Using Campaign 15 data from the K2 mission, we have discovered a triply eclipsing triple star system: EPIC 249432662. The inner eclipsing binary system has a period of 8.23 d, with shallow ∼3 per cent eclipses. During the entire 80-d campaign, there is also a single eclipse event of a third body in the system that reaches a depth of nearly 50 per cent and has a total duration of 1.7 d, longer than for any previously known third-body eclipse involving unevolved stars. The binary eclipses exhibit clear eclipse timing variations. A combination of photodynamical modeling of the light curve, as well as seven follow-up radial velocity measurements, has led to a prediction of the subsequent eclipses of the third star with a period of 188 d. A campaign of follow-up ground-based photometry was able to capture the subsequent pair of third-body events as well as two further 8-d eclipses. A combined photo-spectro-dynamical analysis then leads to the determination of many of the system parameters. The 8-d binary consists of a pair of M stars, while most of the system light is from a K star around which the pair of M stars orbits.